A linked and open dataset from a network of learning repositories on organic agriculture. (7th September 2015) - Rajabi, Enayat; Sanchez‐Alonso, Salvador; Sicilia, Miguel‐Angel; Manouselis, Nikos
Abstract: Exposing eLearning objects on the Web of Data leads to sharing and reusing of educational resources and improves the interoperability of data on the Web. Furthermore, it enriches e‐learning content, as it is connected to other valuable resources using the Linked Data principles. This paper describes a study performed on the Organic.Edunet repository, as an e‐learning portal in an agricultural context. In this research, we experiment with exposing the Organic.Edunet metadata as Linked Open Data and interlinking its contents to several relevant datasets on the Web. An analysis of the metadata and of the interlinking results is presented in this paper as well.